Genetic Diversity in Podophyllum hexandrum Royle from Himachal Pradesh, Northwestern Himalaya, India - Sharma, Abhishek; Sharma, Y. P.; Kumar, Vinod (International Journal of Bio-resource and Stress Management, 2019)
Podophyllum hexandrum belonging to family Berberidaceae is a herbaceous rhizomatous species of great medicinal importance, now endangered in India. Podophyllum hexandrum is a valuable medicinal medicinal herb commonly known as the Himalayan May Apple, grows in the Himalayan alpine and sub alpine zones. It has long been used by the Himalayan natives and the American Indians. Medicinal use of Podophyllum hexandrum dates back to ancient times. Ten representative sites were selected and assessed for its population and genetic diversity. Further, representative plant samples were planted at two different locations for observing the diversity in lamina shapes. Plants of Podophyllum hexandrum were observed to have different number of leaves per plant viz. single leaf, two leaves, three leaves and four leaves per plant. The plant bearing single leaf were more abundant (48.1%) as compared to two leaved (35.4%), three leaved (16.9%) and four leaved plant (0.2%). A mature berry in the single leaved plant was observed for the first time. A considerable morphological variations in the lamina shape of leaf were observed and a total of ten lamina shapes were documented. The lamina shape and number of leaves per plant of most of the plants was found to vary in successive vegetational cycles when observed at two distinct geographical locations. Because the species is threatened at regional and global level, studies of its population biology and genetic diversity are imperative for successful development of its conservation strategies.